Optimalisasi Pemasaran Produk BUMDesa Melalui Pendampingan Pembuatan Platform Digital belanjadesa.id - Sakir, Sakir; Ishak, Aswad; Setianingrum, Reni Budi (Amalee: Indonesian Journal of Community Research and Engagement, 2023)
This community service is to optimize product marketing through assistance in creating a BUMDes digital platform called belanjadesa.id. There are four stages in implementing this program: problem identification, program conceptualization, program implementation, and monitoring and evaluation. The results of the program's performance show that the conceptualization designed two programs that will be implemented: training in operationalizing digital platforms as a marketing method and assisting in creating a digital platform for belanjadesa.id. To carry out the service, all training involves all BUMDes Katon margo Sembada administrators actively. Second, several feature designs in belanjadesa.id provides convenience to buyers, such: as first, there is a login menu to enter the digital platform Belanjadesa. Id to find out the buyer's biodata; second, there is a product type feature to make it easier for buyers to know the type of product being sold; Third, there is product information in the form of descriptions, prices, categories, and product weights to provide information related to the products sold. The output target is expected to increase business and revenue and create a digital culture at BUMDes Katon Margo Sembada to accelerate the economic recovery affected by the Covid-19 pandemic in Margokaton Village.